Decentralized Control for the Cell Power Balancing of a Cascaded Full-Bridge Multilevel Converter - Miguel Vivert; Rafael Diez; Marc Cousineau; Diego Bernal Cobaleda; Diego Patino (Energies, 2023)
This article presents a decentralized control technique applied to a Cascaded Full-Bridge Multilevel Converter (CFBMC) to balance the amount of power provided by its independent cells connected in series. It is based on the use of elementary modular controllers, associated with each converter cell, communicating with their close neighbors to obtain the appropriate power balancing. A complete theoretical study of the system is provided in terms of modal responses, feedback loop bandwidth and stability criteria and the design method of the correctors is explained as well. Each modular controller can be dynamically removed or added to allow reconfiguration of the number of converter cells during operation for functional safety purposes. This method is illustrated with a five-cell CFBMC, studied both with simulations and experimental tests. The response of the system to load transients and cell voltage disturbances demonstrates the robustness of the proposed control method. Thanks to its modularity, the number of voltage levels of the converter can be easily increased by inserting new cells in series without adding complexity to the control part.